Now we’re Cooking with Gas! How Experimental Archaeology Challenges Modern Assumptions about Metal Recycling - E. Giovanna Fregni (EXARC, 2017)
It is accepted knowledge that when re-melting alloys, some of the metal with a lower melting temperature is lost through oxidation, and more metal must be added in order to maintain the desired alloy proportions. In order to understand the changes in alloy content when recycling using Bronze Age technology, experiments were undertaken by the author and others, using a charcoal furnace. These experiments included recycling bronze to quantify loss of tin, and experimentation in co-melting metals. The results were then compared to modern metallurgical practices using electric and gas furnaces. The initial results were presented at the Historical Metallurgy Society’s Research in Progress Conference in November of 2009. However, this paper includes further experiments that build on that work. The conclusions indicate that knowledge of earlier practices was lost with the advance of technology, and that broad assumptions cannot be made about earlier technological practice based on work done with modern equipment.